Our enemies will vanish : the Russian invasion and Ukraine's war of independence - Trofimov, Yaroslav (Penguin Press, 2024)
"Yaroslav Trofimov, the Ukrainian chief foreign-affairs correspondent for The Wall Street Journal, offers an eyewitness account of Russia's 2022 invasion of Ukraine"--